Present and future flooding and erosion along the NW Spanish Mediterranean Coast - Sánchez-Artús, Xavier; Gracia, Vicente; Espino, Manuel; Sierra, Joan Pau; Pinyol, Jordi; Sánchez-Arcilla, Agustín (Frontiers in Marine Science, 2023)
Coastal flooding and eros-ion caused by extreme events are the main factors responsible for beach hazards. This effect will be exacerbated by the sea level rise induced by climate change. The present work determines the vulnerability to erosion and flooding along 55 beaches grouped in different coastal archetypes, representative of the Catalan coast. The vulnerability assessment has been done through the numerical simulation of different combinations for projected waves and mean water levels under present conditions and the climate change scenarios RCP4.5 and RCP8.5 for the year 2100. A storm event approach has been used to determine coastal flooding and erosion with return periods of 50, 100, and 500 years using the XBeach numerical model. Results show that shoreline retreat is not the best proxy to characterize the erosion. The low-lying nature of the coast, the non-presence of well-developed berms, and the existence of river mouth and torrents govern the coastal flooding. The sea level rise appears to be a dominant variable in coastal hazards.